Excision of Hook of Hamate Fractures in Elite Baseball Players: Surgical Technique and Return to Play. Issue 3 (14th March 2022) - Engler, Ian D.; Barrazueta, Gustavo; Colacchio, Nicholas D.; Ruchelsman, David E.; Belsky, Mark R.; Leibman, Matthew D.
Background: Hook of hamate fractures are relatively common in baseball players, but the proper diagnosis and surgical technique can be challenging. Outcomes after surgical excision, as well as optimal surgical technique, in elite baseball players have not been clearly established. Hypothesis: Excision of hook of hamate fractures with a technique tailored to elite professional and collegiate baseball players will lead to high rates of return to play within a short time. Study Design: Case series; Level of evidence, 4. Methods: We reviewed the cases of 42 elite athletes who underwent surgical excision of 42 hook of hamate fractures at a single academic hand surgery practice from 2006 to 2020. The athletes competed at the professional (n = 20) or varsity collegiate (n = 22) baseball levels and were treated using the same surgical technique tailored toward the elite athlete. The clinical history, timing of surgery, complications, and time to return to play were recorded for each patient. Results: All 42 patients underwent an excision of their hook of hamate fracture at a mean of 7.2 weeks (range, 0.5-52 weeks) from the onset of symptoms. All but one patient were able to return to full preinjury level of baseball participation within 6 weeks from the date of surgery, with a mean return to sport of 5.4 weeks (range, 3-8 weeks). Two patients returned to the operating room—1 for scar tissue formation causing ulnar nerve compression and 1 for residual bone fragment causing pain and ulnar nerve compression. Conclusion: Surgical excision of hook of hamate fractures in elite baseball players showed a very high rate of return to play within 6 weeks. Meticulous adherence to the described surgical technique tailored to athletes optimizes clinical outcomes and avoids complications.